2019
DOI: 10.2147/copd.s203715
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of symptom variability on clinical outcomes in COPD: analysis of a longitudinal cohort</p>

Abstract: PurposeWe compared clinical characteristics of COPD patients according to symptom variability and evaluated the effect of symptom variability during the first year of enrollment on clinical outcomes of COPD.MethodsWe analyzed COPD patients’ data from the Korean Obstructive Lung Disease (KOLD) cohort. Symptom variability was defined based on the value of standard deviation (SD) of mMRC scores obtained every 3 months during the follow-up period of the first year. Patients were divided into 2 groups: the consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This type of exacerbations has a similar negative impact on health status as reported exacerbations 52 , so there is no way of knowing if they are real COPD exacerbations or if they just indicate a higher symptom variability period. In this context of uncertainty, some authors have suggested that symptom variability without medication change could be a risk factor for COPD exacerbation and poor prognosis, regardless of lung function and previous exacerbation history 18 .…”
Section: Determinants Of Symptom Variabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…This type of exacerbations has a similar negative impact on health status as reported exacerbations 52 , so there is no way of knowing if they are real COPD exacerbations or if they just indicate a higher symptom variability period. In this context of uncertainty, some authors have suggested that symptom variability without medication change could be a risk factor for COPD exacerbation and poor prognosis, regardless of lung function and previous exacerbation history 18 .…”
Section: Determinants Of Symptom Variabilitymentioning
confidence: 99%
“…Unfortunately, the impact of symptom variability in clinical control has not yet been studied in COPD. However, several studies have reported that early morning symptoms are associated with severe dyspnoea 16,18,43,62 , lower physical activity 43,63 , a higher use of rescue medication 39 , an increase in the number of exacerbations 12,14 or worse HRQoL 14,39 . Nighttime symptoms have also been associated with an increased risk of exacerbations and worse HRQoL 12,14,67,68 .…”
Section: Relevance Of Symptom Variability For Clinical Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Drummond, Wise, & Hansel, 2015). Therefore, in addition to the characteristic respiratory symptoms, such as dyspnea, cough, and expectoration (Kim et al, 2019), they present other extrapulmonary symptoms, such as sleep disorders, fatigue, and muscle weakness (Goërtz et al, 2019;Muñoz, Small, Wood, Ribera, & Nuevo, 2018).…”
mentioning
confidence: 99%